The impacts of roof distributed photovoltaic on rural residents’ carbon emission reduction and power consumption - Qiangfei, Chai; Meirong, Yang; Xintong, Chen (Frontiers in Sustainable Food Systems, 2025)
The development of distributed photovoltaic (PV) on rural rooftops plays an important role in realizing China’s carbon peaking and carbon neutrality goals. Based on a total of 321 rural residents’ electricity consumption panel data containing 28 periods from January 2020 to April 2022, this paper uses a difference-in-difference model to quantitatively analyze the carbon emission reduction effect and changes in rural residents’ electricity consumption behavior before and after the installation of distributed PV. The results show that: the installation of rural residential distributed PV reduces the electricity purchased from the grid by 32.06kWh per month. It brings carbon emission reduction by about 20.97 kgCO2 per month. After installing the PV, there is a significant rebound on the gross electricity consumption of the rural residents which increases by 78.46 kWh. The rebound effect inhibits carbon emission reduction to some extent. There is a short-term sudden increase in the self-consumption of electricity by rural residents after installing PV, and then it gradually decreases. Finally, the proportion of solar power in the gross electricity consumption stabilizes at about 38.4%, which suggests that there is still a lot of room for improvement in rooftop PV utilization rates. The heterogeneity analysis reveals that the rebound effect of installing high-capacity PV users (>20 kVA) is significantly higher than that of low-capacity PV users (<8 kVA).